Product distribution in hydrogenation of styrene oxide over Pd/chitosan catalyst - Viswanadhan, Maya; Potdar, Aparna; Divakaran, Anumon V.; Badiger, Manohar V.; Rode, Chandrashekhar (Research on Chemical Intermediates, 2016)
Palladium-decorated chitosan catalyst was synthesized by an impregnation method by varying the Pd loading in the range of 1-6 %, and was evaluated for the regioselective hydrogenation of styrene oxide. In order to correlate the chemical and textural properties with the catalytic activity, all the prepared catalysts were characterized by techniques such as Fourier transform infrared spectroscopy, X-ray diffraction, scanning electron microscopy, transmission electron spectroscopy, thermo-gravimetric analysis, temperature-programmed desorption of NH3, and CO2 and N-2 physisorption. The synthesized catalysts were utilized for the efficient and regioselective ring opening of styrene oxide by hydrogenation under different conditions. The complete conversion of styrene oxide with 65 % selectivity for 2-phenyl ethanol and 33 % for 1-phenyl ethanol were obtained using 4 % Pd/CS catalyst at 70 degrees C temperature and 3 MPa pressure. The mechanism for the regio selective ring opening of styrene oxide to 1- and 2-phenyl ethanol was also proposed on the basis of properties of the catalyst support, catalytic activity and selectivity. These results indicated that the catalytic activity and selectivity of the catalysts were affected by the nature of support. Further, the basic properties of the support play an important role in the selectivity of the styrene oxide hydrogenation reaction.

Pyridine immobilised on magnetic silica as an efficient solid base catalyst for Knoevenagel condensation of furfural with acetyl acetone - Tarade, Komal; Shinde, Suhas; Sakate, Sachin; Rode, Chandrashekhar (Catalysis Communications, 2019)
Novel heterogeneous pyridine immobilised magnetic silica (Fe3O4@SiO2-Py) was found to be an efficient, greener and heterogeneous solid base catalyst for the Knoevenagel condensation of furfural with acetylacetone under optimized reaction conditions. The Knoevenagel condensation product 3-(2-furylmethylene)-2,4-pentanedione (FMP), a jet fuel precursor, was produced in high yield of 85% with 94% conversion of furfural at 100 degrees C within a period of 4 h. Fe3O4@SiO2-Py catalyst showed excellent stability and recyclability without losing its initial activity.
Keywords: furfural; Jet fuel; Knoevenagel condensation; Silica immobilised pyridine; Solid base